The impact of village heads' educational levels on adolescent academic performance: Evidence from rural China. - Jing Li; Huan Deng; Jun Li (PLoS ONE, 2025)
This study investigates the relationship between the educational level of village heads and the academic performance of adolescents, using data from the China Family Panel Studies (CFPS). The analysis reveals that village chiefs with well-educated significantly enhance the academic outcomes of adolescents within their communities. This positive effect remains robust even after controlling for endogeneity through instrumental variables and conducting various robustness checks. Further investigation shows that these well-educated village leaders contribute to an increased provision of public goods, thereby improving the village's external environment, which in turn supports academic performance. Additionally, well-educated village chiefs serve as role models within the community's social network, positively influencing parental educational aspirations and enhancing adolescents' academic results. Notably, the impact of well-educated village chiefs is more pronounced among girls and adolescents from low-income families, underscoring its significance in promoting gender equity in education and breaking cycles of intergenerational poverty.